Pacientes renais crônicos em hemodiálise e atendimento psicológico: revisão de escopo e reflexão segundo o referencial psicanalítico - Di Lollo, Maria Cristina (2021)
The result of the 20 years clinical experience of psychological support for patients with chronic kidney disease in hemodialysis, and due to the lack of literature about psychological support for such patients, particularly studies using the theoretical and technical foundation of psychoanalysis, the present study is justified by the high prevalence of this disease in the population and by it’s countless signs of psychological distress. The objective was to identify the status of the knowledge about psychological support for patients with chronic kidney disease and to reflect on the contribution of psychoanalysis in this context. A literature review, based on the scoping review methodology of Instituto Joanna Briggs, was conducted to identify publications about psychological support to patients with chronical kidney disease in hemodialysis, using the databases PubMed, LILACS, CINAHL, EMBASE and PsycINFO. Documents pertaining to grey literature were also considered. The final sample was composed by 23 articles. The studies found were using diferent theoretical and technical foundations and different types of psychological interventions, and all of them reportedly identified improvement of psychic symptoms, coping and adaptation to the treatment and the new life conditions. Among the studies that composed the sample, a number of them were using cognitive behavior theory (N=7), behavior analysis (N=2), psychoanalytic oriented psychotherapy (N=2), positive psychology (N=1), among others. On the kind of studies identified, there were mostly studies with descriptive study characteristics (N=5), randomized experimental studies (N=3), case studies (N=3), studies with experimental report characteristics (N=3), studies with quasi-experimental characteristics (N=2), single-group clinical studies (N=2) and experimental reports (N=2). In general, the studies report improvements in quality of life, in the symptoms of distressed mood and depression, and improvement in clinical and mental health. However, the methodological characteristics of the studies are not enough to generate strong evidence and allow safe generalizations, which indicates the need for production of more studies about the subject. This study also presents reflection on the psychoanalytic psychosomatics and its possible contributions, by means of psychological support to patients with chronic kidney disease in hemodialysis, based on the promotion of affect representation and symbolization. The conclusion is that, in general, the knowledge produced and published in the consulted databases, about psychological support to patients with chronic kidney disease, indicates a lack of studies and methological gaps, with an absence, for example, of longitudinal studies or others performed with more expressive samples of patients. It was also identified the need for greater methodological rigor in relation to the psychological interventions performed, with the presentation of more consistent conceptual and operational definitions.